2016
DOI: 10.1097/ccm.0000000000001475
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Dietary Restriction Rescues Mice From Lethal Abdominal Sepsis and Endotoxemia and Reduces the Inflammatory/Coagulant Potential of Adipose Tissue

Abstract: Objective Visceral adipose tissue is a major site for expression of pro-inflammatory and pro-coagulant genes during acute systemic inflammation. In this study, we tested whether loss of fat mass by dietary restriction (DR) would remove the major source of these factors resulting in improved tolerance to sepsis and endotoxemia. Design Prospective, laboratory controlled experiments. Setting Aging and Critical Care Research Laboratory in a university hospital. Subjects Middle-aged (12 month-old) male C57BL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 45 publications
0
23
0
2
Order By: Relevance
“…In rodent models of various diseases, caloric restriction significantly attenuated inflammatory response 34 . The present study showed that the measured cytokines increased over time in serum, peri-incisional skin tissue and ipsilateral spinal cord dorsal horn, accompanied by increased GPS and decreased PWMT and PWTL after incision in rats fed ad libitum .…”
Section: Discussionmentioning
confidence: 99%
“…In rodent models of various diseases, caloric restriction significantly attenuated inflammatory response 34 . The present study showed that the measured cytokines increased over time in serum, peri-incisional skin tissue and ipsilateral spinal cord dorsal horn, accompanied by increased GPS and decreased PWMT and PWTL after incision in rats fed ad libitum .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is highly reproducible using our new CS preparation protocol (22, 29). Using this model, we showed that bacteria are not always detectable in the circulation of animals until 12 hours after injection with a lethal dose of CS.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the recent diet westernization of developing countries has been associated with an increased prevalence of inflammatory or autoimmune disorders (Manzel et al, 2014). In contrast, reduced caloric intake is associated with improved outcomes for metabolic, autoimmune and inflammatory diseases, including NAFLD (Kani et al, 2017), T2DM , CVD (Wei et al,10 2017), multiple sclerosis (Choi et al, 2016;Jahromi et al, 2014), rheumatoid arthritis (Choi et al, 2017;Kjeldsen-Kragh et al, 1991), asthma (Johnson et al, 2007), psoriasis (Jensen et al, 2016), colitis (Shibolet et al, 2002), and sepsis (Starr et al, 2016;Wannemacher et al, 1979) and has been shown to prolong the lifespan of rodents, monkeys, and humans (Fontana et al, 2010;Picca et al, 2017). However, the molecular mechanisms by which caloric restriction 15 modulates systemic inflammation remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%